The preparation and characterization of multinuclear catalysts based on novel dendrimers : application in the oligomerization and polymerization of unsaturated hydrocarbons - Malgas-Enus, Rehana (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD)--University of Stellenbosch, 2011.